Identification of hot springs in Sungai Pinang using the Schlumberger configuration geoelectric method - Lily Wandari; Usman Malik (Universitas Riau, 2024)
One of the hot spring tourist attractions in Riau Province is Sungai Pinang Village, Hulu Kuantan District, Kuantan Singingi Regency. The geothermal system at that location originates from a geological structure where faults and fractures are pathways for the transfer of geothermal fluids, so it is necessary to identify hot springs. This study aimed to determine the resistivity value of rock layers and to find out the test results for hot water sample content using pH and temperature parameters. The method used is the Schlumberger configuration geoelectric method. Data processing was carried out using progress software with the one-dimensional data type. The resistivity value of the rocks obtained in line 1 has a resistivity range of 39.77 – 594.04 Ωm with a depth of 0 – 23.02 m. Track 2 has resistivity values ranging from 28.41 – 2585.18 Ωm with a depth of 0.29 – 1.06 m. Track 3 has resistivity values ranging from 2.76 – 856.53 Ωm with a depth of 0 – 7.82 m. Interpretation results on tracks 1 and 2 found no hot water because the track's position is far from the hot springs. Hot water is found on track 3 with depths ranging from 0 – 0.04 m and 3.76 – 7.82 m.